PENGARUH PENDEKATAN PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS ANAK USIA 5-6 TAHUN DI TK PERTIWI SELONG - Aripatun; Ika; Putu Nina , Ni Luh; Era, Filsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this industrial era 4.0, the ability of science process skills is a very necessary ability as one of the competencies that must be learned for basic science skills for early childhood. However, learning in PAUD has not provided many opportunities for students to learn science process skills. This study aims to determine whether there is an influence on the science process skills of children aged 5-6 years at Pertiwi Selong Kindergarten by using the Project Based Learning (PjBL) model conducted at Pertiwi Selong Kindergarten. This research uses a quantitative research approach, type of quasi-experimental research with nonequivalent control group research designs. The instrument in this study used a science process skills test, in the form of a non-test in the form of an observation sheet. The population in this study amounted to 73 children. while the sample in this study amounted to 32 children. based on the results of the study, the data calculated by the independent t-test test using IBM SPSS Statistics 25 showed that the Sig. (2 tailed) value was 0.00 <0.05. So, it can be concluded that Ha is accepted, meaning that there is an effect of the Project Based Learning learning approach on the science process skills of children aged 5-6 years at Pertiwi Selong Kindergarten.